KARAKTERISTIK PERUSAHAAN TERHADAP PENGUNGKAPAN INTELLECTUAL CAPITAL PADA PERBANKAN SYARIAH DENGAN UMUR PERUSAHAAN SEBAGAI MODERASI - Brigitta Gilang Kinanti; Rico Elhando Badri (LP2M Universitas Bina Bangsa, 2021)
There are many companies that have not disclosed information regarding the intellectual capital disclosure because there are no obligations or standards governing it, so that the intellectual capital disclosure is now getting enough attention from various parties. The purpose of this study was to determine the effect of leverage, managerial ownership and company size on the disclosure of intellectual capital with the company age as the moderation in Islamic banking companies in the period of 2016-2020. This study used the associative method with the hypothesis testing using Moderating Regression Analysis (MRA). The results of this study indicated that the results of the calculation of the t-test (partial) showed that partially the variable leverage, managerial ownership and company size had a significant effect on the disclosure of Islamic banking intellectual capital in 2016-2020, while the interaction variable age and leverage (X1_M) had no significant effect on the intellectual capital disclosure. The interaction between age and managerial ownership (X2_M) did not have a significant effect on the intellectual capital disclosure, while the interaction between age and firm size (X3_M) had a significant effect on the intellectual capital disclosure. This indicated that the size of the company age when it had a high company size made it willing to disclose its intellectual capital so that investors would certainly be interested in investing in large companies.